VSTOL FCS using nonlinear dynamic inversion and scheduled fixed wing controllers - Bayliss, Martin T.; Verspecht, T.; Whidborne, James F. (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This paper describes the application of input-output Nonlinear Dynamic Inversion (NDI) to flight control of a tilt-rotor actuated Vertical Short Take Off and Landing (VSTOL) platform. The NDI formulation is performed in the inertial reference frame resulting in a decoupled and linearised set of integrator virtual plants controlled using Linear Quadratic Integral (LQI) control. The NDI controller is continuously enabled along with a conventional fixed wing controller with the latter scheduled in and out of control authority as a function of the wing tilt/vector angle control input generated by the NDI controller.
Keywords: State feedback; Schedules; Nonlinear dynamical systems; Calibration; Aerospace control